Дослідження на посаді Новобогородицької фортеці - Шалобудов, В.М.; Ковальова, І.Ф. (Археологічні дослідження в Україні, 2010)
Described are the graves of necropolis discovered during the work of the Expedition of the Laboratory of the Dnipro River Region Archaeology of the O. Honchar Dnipropetrovsk National University at posad (trading quarter) of Novobohorodytska fortress.